Adverse Events Following Administration of Anti-CTLA4 Antibody Ipilimumab - Karimi, Amirali; Alilou, Sanam; Mirzaei, Hamid Reza (Frontiers in Oncology, 2021)
Ipilimumab, a monoclonal anti-CTLA4 antibody, paved the path for promising treatments, particularly in advanced forms of numerous cancers like melanoma. By blockading CTLA-4, ipilimumab can abolish the higher binding affinity of B7 for CTLA-4, setting CD28 free to act unlimited. This blockade can result in an amplified antitumor immune response, and thereby, boosting more effective tumor regression. However, this blockage can lead to diminished self-tolerance and yielding autoimmune complications. The current review aims to describe adverse events (AEs) following the administration of ipilimumab in different cancers as every benefit comes at a cost. We will also discuss AEs in two different categories, melanoma and non-melanoma, owing to the possible shining promises in treating non-melanoma cancers. As the melanoma settings are more studied than other cancers, it might even help predict the patterns related to the other types of cancers. This similarity also might help physicians to predict adverse events and correctly manage them in non-melanoma cancers using the extensive findings reported in the more-studied melanoma settings. Recognizing the adverse events is vital since most of the adverse events could be reverted while carefully implementing guidelines. Finally, we will also describe the observed effectiveness of ipilimumab in non-melanoma cancers. This effectiveness reveals the importance of understanding the profile of adverse events in this group, even though some have not received FDA approval yet. Further clinical trials and careful systematic reviews may be required to decipher the hidden aspects of therapies with ipilimumab and its related AEs.